Sistem Pendukung Keputusan Penerimaan Pegawai PT. Andalusia Nur Ramadhan dengan Metode Simple Additive Weighting - Bramantara Yudha (Jurnal Informatika Universitas Pamulang, 2020)
The purpose of the hiring decision support system is to assist and speed up the decision-making process. There are so many methods that companies can apply in determining employee acceptance to rank prospective employees according to the results of the assessment, examples of methods that can be used are the SAW method or Simple Additive Weighting using the Java Netbeans application and the MySQL database. This research produces a system that can assist in providing decision support for hiring employees. So as to help the main director to determine and select employees who are accepted by the company PT. Andalusia Nur Ramadhan.